Ethnicity and Party Systems in Francophone Sub-Saharan Africa - Matthias Basedau; Alexander Stroh (German Institute of Global and Area Studies (GIGA), 2009)
Despite earlier assumptions that ethnicity is a central feature of African party systems, there is little substantial evidence for this claim. The few studies with an empirical foundation rarely rely on individual data and are biased in favor of Anglophone Africa. This paper looks at four Francophone countries, drawing on four representative survey polls in Benin, Burkina Faso, Mali, and Niger. Multivariate regression models and bivariate control tools reveal that ethnicity matters as a determinant of party preference, but that its impact is generally rather weak and differs with regard to party systems and individual parties. 'Ethnic parties' in the strict sense are almost completely absent, and only the Beninese party system is substantially 'ethnicized'. In particular, regional ties between voters and leaders - rather than ethnic affiliation alone - deserve attention in the future study of voting behavior in Africa. – – Die verbreitete Annahme, dass Ethnizität ein zentrales Charakteristikum afrikanischer Parteiensysteme sei, konnte bisher nicht überzeugend belegt werden. Die wenigen verfügbaren Studien mit empirischer Grundlage können nur selten Individualdaten nutzen. Zudem wird das frankophone Afrika kaum berücksichtigt. Der vorliegende Beitrag antwortet auf beide Defizite mit einer vergleichenden Analyse repräsentativer Meinungsumfragen aus den vier frankophonen Ländern Benin, Burkina Faso, Mali und Niger. Multivariate Regressionsmodelle und bivariate Kontrollinstrumente zeigen, dass Ethnizität die Wahlabsicht im Allgemeinen nur schwach und nach Untersuchungsfällen variabel beeinflusst. 'Ethnische Parteien' in einem engeren Sinne kommen fast gar nicht vor und nur das beninische Parteiensystem ist beträchtlich ethnisiert. Künftige Forschung ist aufgefordert, insbesondere regionalen Wählerbindungen mehr Aufmerksamkeit zu schenken, statt vorwiegend nach ethnischem Wahlverhalten zu suchen.
Keywords: 300; political parties; ethnic groups; voting intentions; multivariate logistic regression